Electrolyte-doped sulfur / carbon composite cathode material and preparation method thereof
Patent Information
- Application Number
- CN202310869930.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-14
- Filing Date
- 2023-07-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-07-17
Smart Images

Figure CN116826001B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical power sources, specifically relating to an electrolyte-doped sulfur / carbon composite cathode material, its preparation method, and its application. Background Technology
[0002] In recent years, with the depletion of natural resources such as oil and coal, and the urgent need for high-energy-density rechargeable batteries with high safety and rapid charge / discharge capabilities, the development of a new generation of battery systems that combine high energy density, high power density, and high stability is imperative. Among anode materials, lithium metal has the lowest potential (-3.04 V relative to the standard hydrogen electrode) and an extremely high theoretical specific capacity (3860 mAh g⁻¹). -1 Sulfur cathodes have received considerable attention due to their high theoretical specific capacity (1675 mAh g⁻¹). -1 Environmentally friendly and abundant, lithium metal anodes can theoretically achieve an energy density of up to 2600 kWh / kg. -1 Therefore, lithium-sulfur batteries are considered the most promising high-energy-density battery system of the next generation. However, the practical application of lithium-sulfur batteries still faces many problems. For example, elemental sulfur and insoluble Li₂S are electronic and ionic insulators, requiring highly conductive materials to utilize their activity. During sulfur reduction, polysulfides are generated that easily dissolve in the electrolyte, causing a shuttle effect. Furthermore, sulfur undergoes approximately 79% volume expansion when converted to Li₂S. These problems lead to the loss of active material in the positive electrode and kinetic stagnation during charge and discharge, thus reducing the energy density of lithium-sulfur batteries. In particular, the shuttle effect of polysulfides between the positive and negative electrodes causes overcharging, electrolyte consumption, and corrosion of the lithium negative electrode, ultimately leading to battery failure.
[0003] To address the aforementioned problems, various porous conductive carbon materials and catalysts have been applied to lithium-sulfur batteries. For example, loading sulfur into porous carbon materials can utilize van der Waals interactions to adsorb polysulfides and suppress polysulfide shuttle. However, polar polysulfides cannot be firmly bound within porous materials, and polysulfide shuttle inevitably occurs. Introducing heteroatoms into porous carbon materials effectively enhances the interaction between carbon materials and polysulfides; however, these methods do not fundamentally solve the problems of lithium-sulfur batteries, and the accumulation of polysulfides can lead to deactivation of active sites. Therefore, based on the principles of catalysis, introducing catalysts into the positive electrode to accelerate the conversion between soluble polysulfides and insoluble Li₂S is considered a very promising strategy for fully utilizing active materials. Summary of the Invention
[0004] To address the shuttle effect and slow sulfur conversion kinetics in lithium-sulfur battery systems, an ultrafast lithium-ion pathway for sulfur was constructed by introducing a lithium solid electrolyte with ultra-high room-temperature ionic conductivity and a wide electrochemical window into the sulfur cathode. This mitigated the decrease in ionic conductivity caused by the dissolution of polysulfides, effectively suppressed polysulfide shuttle, accelerated the conversion of polysulfides to Li2S, solved the problem of active material loss during lithium-sulfur battery cycling, and improved the utilization rate of active material and the cycle stability of the battery.
[0005] The present invention achieves its objective through the following technical solution:
[0006] This invention first provides an electrolyte-doped sulfur / carbon composite cathode material, wherein the composite cathode material comprises a sulfur / carbon composite doped with a lithium solid electrolyte selected from Li 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO), Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP), Li 1.4 Al 0.4 Ti 1.6 (PO4)3 (LATP), Li 0.55 La 0.35 One or more of TiO3.
[0007] Preferably, the sulfur / carbon composite cathode material further comprises conductive additives, binders, and dispersants. Based on the total mass of the composite cathode material, the proportion of the sulfur / carbon composite doped with lithium solid electrolyte is 60-99 wt%, the proportion of conductive additives is 0.5-15 wt%, the proportion of binders is 0.5-15 wt%, and the content of dispersants is 0-10 wt%. Preferably, the proportion of the sulfur / carbon composite doped with lithium solid electrolyte can be 70-80 wt%, 75-85 wt%, or 80-90 wt%. Preferably, the proportion of conductive additives is 1-3 wt%, 3-5 wt%, 3-8 wt%, 5-8 wt%, or 5-10 wt%. Preferably, the proportion of binders is 2-5 wt%, 5-10 wt%, or 5-15 wt%. Preferably, the proportion of dispersants is 1-5 wt%.
[0008] Preferably, the conductive additive is selected from one or more of Super P, Ketjen Black, graphene, and conductive carbon nanotubes. The binder is selected from one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber / sodium carboxymethyl cellulose (CMC / SBR), sodium alginate (SA), and gelatin. The solvent is selected from one or more of N-methylpyrrolidone, ethanol, and water.
[0009] Preferably, the porous carbon in the sulfur / carbon composite is selected from one or more of Super P, Ketjenblack, graphene, carbon nanotubes, mesoporous CMK3, and carbon fibers. More preferably, the porous carbon is one of Ketjenblack, graphene, carbon nanotubes, and mesoporous CMK3.
[0010] Preferably, the lithium solid electrolyte is pretreated by coating with a mixed solution of polymer coating agent and lithium salt. Preferably, the mass ratio of lithium solid electrolyte, polymer coating agent and lithium salt is 100:1-10:1-10, more preferably 100:2-5:2-5.
[0011] Preferably, the carbon is porous carbon, and sulfur is wholly or at least partially embedded in the porous carbon.
[0012] Preferably, the mass content of the lithium solid electrolyte in the electrolyte-doped sulfur / carbon composite cathode material is 1-30%, more preferably 5-10%.
[0013] This invention also provides a method for preparing an electrolyte-doped sulfur / carbon composite cathode material, characterized by comprising the following steps:
[0014] (S1) The sulfur / carbon composite is prepared by grinding or ball milling sulfur and porous carbon, heating the resulting mixture at 150℃-170℃ for 4-12 hours under vacuum or in an argon-filled environment, and then naturally cooling it to room temperature (e.g., 20-25℃) to obtain the sulfur / carbon composite.
[0015] (S2) The lithium solid electrolyte is ground and mixed with the sulfur / carbon composite obtained in step S1 to obtain the lithium solid electrolyte-doped sulfur / carbon composite, and then mixed with conductive additives, binders and dispersants to obtain the electrolyte-doped sulfur / carbon composite cathode material.
[0016] The lithium solid electrolyte is selected from Li 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO), Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP), Li 1.4 Al 0.4Ti 1.6 (PO4)3 (LATP), Li 0.55 La 0.35 One or more of TiO3.
[0017] Preferably, the lithium solid electrolyte is pretreated by a mixed solution of a polymer coating agent and a lithium salt; more preferably, the polymer coating agent is selected from polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), polyoxyethylene ether (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile layer (PAN), polydopamine (PVA), polyvinyl alcohol (PVA), polycaprolactone (PCL), polyvinyl carbonate (PEC), polypropylene carbonate (PPC), polymethyl methacrylate (PMMA), lithium polystyrene sulfonate (PLSS), and poly(ethylene glycol) methyl ether methacrylate. (PEGMEA) and polyethylene glycol acrylate (PEGDA), wherein the most preferred is lithium polystyrene sulfonate (PLSS); the lithium salt is selected from lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium bis(oxalate-borate) (LiBOB), lithium difluorooxalate-borate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), wherein the most preferred are lithium bis(difluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0018] The present invention also provides an electrolyte-doped sulfur / carbon composite cathode, which is prepared by coating the aforementioned electrolyte-doped sulfur / carbon composite cathode material or the electrolyte-doped sulfur / carbon composite cathode material obtained by the aforementioned preparation method onto the surface of a current collector.
[0019] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that the positive electrode is a sulfur / carbon composite positive electrode doped with the aforementioned electrolyte.
[0020] Preferably, the separator is pretreated by mixing a lithium solid electrolyte pretreated with a polymer coating agent and a lithium salt with a conductive additive and a binder, and then coating the mixture onto one surface of the separator to obtain a pretreated separator, wherein the pretreated surface of the separator is in contact with the positive electrode. More preferably, the polymer coating agent used for the pretreated separator is the same as the polymer coating agent used for coating the pretreated lithium solid electrolyte; the lithium salt used for the pretreated separator is the same as the lithium salt used for coating the pretreated lithium solid electrolyte. That is, the polymer coating agent is selected from polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), polyoxyethylene ether (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile layer (PAN), polydopamine (PVA), polyvinyl alcohol (PVA), polycaprolactone (PCL), polyvinyl carbonate (PEC), polypropylene carbonate (PPC), polymethyl methacrylate (PMMA), lithium polystyrene sulfonate (PLSS), poly(ethylene glycol) methyl ether methacrylate (PEGMEA), and polyethylene glycol acrylate (PEG). The lithium salt is selected from lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium bis(oxalateborate) (LiBOB), lithium difluorooxalateborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI), or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), with the most preferred being lithium bis(difluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0021] Furthermore, the negative electrode is selected from lithium metal negative electrode, silicon negative electrode, graphite negative electrode, or a combination thereof.
[0022] Furthermore, the diaphragm is selected from one of polyethylene diaphragm, polypropylene diaphragm, polyethylene / polypropylene composite diaphragm, hydroxymethyl cellulose, or cellulose acetate.
[0023] In addition, the present invention also provides the application of the lithium-sulfur battery in energy storage devices.
[0024] In addition, the present invention also provides the application of the lithium solid electrolyte doping in lithium-sulfur battery cathode materials to improve the cycle stability and coulombic efficiency of lithium-sulfur batteries.
[0025] The beneficial effects of this invention are at least as follows:
[0026] (1) The lithium solid electrolyte selected in this invention has a significant adsorption effect on polysulfides, which improves the shuttle problem in lithium-sulfur batteries. In addition, the lithium solid electrolyte has high room temperature ionic conductivity and a wide electrochemical window, which constructs an ultrafast lithium ion pathway of sulfur in the positive electrode, alleviates the decrease in ionic conductivity caused by the dissolution of polysulfides, improves the reaction kinetics of the battery, and thus improves the rate performance and cycle performance of the battery.
[0027] (2) Preferably, the lithium solid electrolyte is pretreated by a mixed solution of polymer coating agent and lithium salt, thereby reducing the agglomeration of lithium solid electrolyte and improving ionic conductivity.
[0028] (3) Preferably, the surface of the separator in contact with the positive electrode is also pretreated, wherein the polymer coating agent and lithium salt pretreated lithium solid electrolyte are mixed with conductive additives and binders and then coated onto one surface of the separator, further reducing the shuttle of polysulfides and promoting the conversion of long-chain polysulfides to short-chain polysulfides, thereby improving the rate performance and cycle performance of the battery. Attached Figure Description
[0029] Figure 1 This is an SEM image of the pretreated lithium solid electrolyte in Example 1.
[0030] Figure 2 The image shows the XRD pattern of the pretreated lithium solid electrolyte in Example 1.
[0031] Figure 3 These are TEM and EDS mapping images of the pretreated lithium solid electrolyte in Example 1.
[0032] Figure 4 This is a SEM image of the electrolyte-doped sulfur / carbon composite cathode material in Example 1.
[0033] Figure 5 An optical photograph of the adsorption of Li2S6 on the pretreated lithium solid electrolyte prepared in Example 1.
[0034] Figure 6 The UV-vis spectrum of Li2S6 was measured after the supernatant of the pretreated lithium solid electrolyte in Example 1 was taken after standing in the adsorption experiment.
[0035] Figure 7 The charge-discharge curves of the lithium-sulfur battery obtained in Example 1 are shown.
[0036] Figure 8 The charge-discharge curves of the lithium-sulfur battery obtained in Comparative Example 1 are shown. Detailed Implementation
[0037] (I) Preparation of sulfur / carbon / LLZTO@P (VDF-HFP) composite electrode and its application in lithium metal batteries
[0038] (S1)Li 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO (Lithium Hydroxide) is produced using lithium hydroxide, lanthanum oxide, zirconium dioxide, and tantalum pentoxide as raw materials. The raw materials are weighed according to stoichiometric ratios and ball-milled at 500 rpm for 6 hours in isopropanol solvent. After drying the isopropanol in a 70°C forced-air oven, the resulting powder is cold-pressed into sheets, covered with master powder, and calcined at 950°C for 6 hours at a heating rate of 2.5°C / min. The calcined sheets are then ground into powder, and the ball milling and calcination steps are repeated. The sheets obtained after the second calcination are ground into powder and ball-milled in isopropanol solvent for 4 hours to obtain LLZTO nanoparticles.
[0039] The sulfur / carbon composite was prepared by grinding or ball milling sulfur and porous carbon, heating the resulting mixture at 155°C for 6 hours in an argon-filled environment, and then naturally cooling it to room temperature.
[0040] (S2) P(VDF-HFP) and LiFSI were dissolved in dimethyl sulfoxide (DMSO) at a mass ratio of 3:2 and stirred until homogeneous to obtain a uniform P(VDF-HFP) / LiFSI / DMSO solution. The P(VDF-HFP) / LiFSI / DMSO solution and the prepared LLZTO nanoparticles were then subjected to high-energy ball milling to ensure thorough mixing, with the LLZTO to P(VDF-HFP) mass ratio being 100:5. Isopropanol was added as a precipitant to ensure uniform deposition of the polymer P(VDF-HFP) on the surface of the LLZTO particles. The product was then transferred to a vacuum oven and dried overnight at 60°C to remove the solvent, resulting in LLZTO@P(VDF-HFP) / LiFSI lithium solid electrolyte powder. The obtained LLZTO@P(VDF-HFP) / LiFSI lithium solid electrolyte powder was stored in an argon-filled glove box. Figure 1 The image shows the morphology of the pre-coated LLZTO particles, revealing that their size is at the nanometer scale. Figure 2 The XRD results of the prepared composite lithium solid electrolyte powder were consistent with those of LLZTO powder, indicating that the coating of P(VDF-HFP) / LiFSI had no effect on the structure of LLZTO. The EDS image from TEM showed that P(VDF-HFP) / LiFSI was uniformly dispersed on the LLZTO surface. Figure 3 ).
[0041] (S3) The obtained LLZTO@P (VDF-HFP) / LiFSI lithium electrolyte powder was mixed with a sulfur / carbon composite at a mass ratio of 1:10 and thoroughly ground to obtain a sulfur / carbon / LLZTO@P (VDF-HFP) / LiFSI composite material. This composite material was then mixed with a conductive additive (Super P) and a binder, polyvinylidene fluoride (PVDF), at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) was added as a dispersant (50 wt% of the binder). After thorough grinding, the mixture was uniformly coated onto the surface of a carbon-coated aluminum foil. It was then dried in a 60℃ oven for 24 hours to obtain the composite cathode. Figure 4 The image shows a SEM image of a sulfur cathode with added LLZTO@P(VDF-HFP) / LiFSI electrolyte powder. The image shows that the introduction of LLZTO@P(VDF-HFP) / LiFSI has no effect on the morphology of the cathode.
[0042] (S4) The prepared composite positive electrode is cut into small circular pieces with a diameter of 10 mm. Under high-purity argon gas, the 10 mm diameter circular pieces are used as the positive electrode in the battery casing, followed by the Celgard separator and lithium negative electrode stacked sequentially. Then, an electrolyte is added dropwise, consisting of ethylene glycol dimethyl ether and 1,3-dioxolane in a 1:1 weight ratio, with LiNO3 as the additive and lithium bis(trifluoromethanesulfonic acid)imine lithium (LiTFSI) (molar concentration of 1 M). The battery casing is then completely sealed, and battery performance is tested.
[0043] (II) Test of the adsorption effect of LLZTO@P (VDF-HFP) / LiFSI powder on Li2S6
[0044] LLZTO@P(VDF-HFP) / LiFSI powder was added to a 0.5 mM Li₂S₆ solution, and from... Figure 5 The study observed that after standing for 12 hours, the Li₂S₆ solution with added LLZTO@P(VDF-HFP) / LiFSI became colorless and transparent, while the original Li₂S₆ solution remained yellow. This indicates that LLZTO@P(VDF-HFP) / LiFSI has an adsorption effect on Li₂S₆. The supernatant of the above solution was then measured for UV-Vis absorption spectra. Figure 6 The absorption peak intensity of Li2S6 in the supernatant of Li2S6 with added LLZTO@P(VDF-HFP) / LiFSI was significantly reduced.
[0045] (III) Performance Testing of Lithium Metal Batteries
[0046] The electrochemical performance of the battery was tested using the Blue Electric testing system. The test temperature was 25°C, and the battery capacity and charge / discharge current were calculated based on the mass of sulfur. Figure 7The charge-discharge curves of the battery in Example 1 at a 0.2C rate are shown in Table 1. The first-cycle discharge capacity, first-cycle coulombic efficiency, discharge capacity after 20 cycles, and capacity retention are recorded. The test results of the obtained battery are listed in Table 1.
[0047] Example 2
[0048] The other conditions were the same as in Example 1, except that lithium styrene sulfonate (PLSS) was used instead of P(VDF-HFP) lithium solid electrolyte, resulting in LLZTO@PLSS / LiFSI.
[0049] Example 3
[0050] The other conditions are the same as in Example 1, except that the diaphragm used in step (S4) is treated as follows:
[0051] The LLZTO@P(VDF-HFP) / LiFSI lithium solid electrolyte powder obtained in step (S2) is uniformly coated onto the separator with Super P and PVDF at a mass ratio of 5:4:1, with a coating thickness of 10 μm.
[0052] Example 4
[0053] The other conditions are the same as in Example 1, except that the coating material in step (S2) is PEO.
[0054] Example 5
[0055] The other conditions are the same as in Example 1, except that the coating material in step (S2) is PVDF.
[0056] Example 6
[0057] The other conditions are the same as in Example 1, except that the lithium solid electrolyte in step (S1) is LATP.
[0058] Example 7
[0059] The other conditions are the same as in Example 1, except that the lithium solid electrolyte in step (S1) is LAGP.
[0060] Example 8
[0061] The other conditions are the same as in Example 1, except that in step (S2), LiTFSI is used instead of LiFSI.
[0062] Example 9
[0063] The other conditions are the same as in Example 2, except that in step (S2), LiTFSI is used instead of LiFSI.
[0064] Comparative Example 1
[0065] Battery fabrication using the original sulfur / carbon composite as the positive electrode:
[0066] Step 1) After thoroughly grinding the obtained sulfur / carbon composite with the conductive additive (Super P), it is mixed with the binder vinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is added as a dispersant, and after thorough grinding, it is uniformly coated onto the surface of carbon-coated aluminum foil. It is then dried in an oven at 60℃ for 24 hours to obtain a sulfur cathode.
[0067] Step 2) Under high-purity argon gas, in the battery casing, using the aforementioned 10mm diameter disc as the positive electrode, the Celgard separator and lithium negative electrode are stacked sequentially. Additionally, an electrolyte solution consisting of ethylene glycol dimethyl ether and 1,3-dioxolane (by weight ratio) in a 1:1 ratio, with LiNO3 as an additive, and lithium bis(trifluoromethanesulfonic acid)imide (LiTFSI) (1M molar concentration) as the solute is added. The battery casing is then completely sealed, and battery performance testing is performed. Figure 8 The charge-discharge curves of the battery obtained for this comparative example are shown.
[0068] Comparative Example 2
[0069] The other conditions are the same as in Example 1, except that lithium nitrate is used instead of LLZTO for the lithium solid electrolyte.
[0070] Application example: Performance testing of lithium metal batteries
[0071] The electrochemical performance of the batteries was tested using a battery testing system. The test temperature was 25℃, and the battery capacity and charge / discharge current were calculated based on the mass of sulfur. The first-cycle discharge capacity, first-cycle coulombic efficiency, discharge capacity after 100 cycles, and capacity retention were recorded. The test results of the obtained batteries are listed in Table 1.
[0072] Table 1 Performance data of the examples and comparative examples
[0073]
[0074] Comparing Example 1 with Comparative Example 1, it can be seen that the lithium solid electrolyte of the present invention, which uses a specific type of pre-coated lithium electrolyte, can not only adsorb polysulfides, thereby preventing polysulfide shuttle, but also add it to the sulfur cathode to construct an ultrafast lithium ion conduction path from the cathode to the electrolyte.
[0075] In summary, this invention creatively provides a sulfur / carbon / composite electrolyte composite electrode, employing a lithium solid electrolyte compatible with a sulfur cathode and possessing high ionic conductivity. During battery operation, the introduced lithium solid electrolyte not only provides continuous electron and lithium-ion conduction in the localized areas in contact with the active material, promoting sulfur redox and maximizing the utilization of the active material, but also exhibits a strong adsorption effect on polysulfides, reducing the shuttle effect of soluble polysulfides. Benefiting from these characteristics, the cycle stability and coulombic efficiency of the lithium-sulfur battery are significantly improved. Based on this, this invention provides a new application approach for lithium solid electrolytes, offering new ideas for the design and research of future high-performance lithium-sulfur battery cathode materials and promoting the development of solid-state lithium-sulfur batteries.
Claims
1. A lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode is prepared by coating a sulfur / carbon composite positive electrode material doped with an electrolyte onto the surface of a current collector; the composite positive electrode material contains a sulfur / carbon composite doped with a lithium solid electrolyte, wherein the lithium solid electrolyte is selected from Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 0.55 La 0.35 One or more of TiO3; the lithium solid electrolyte is pretreated by coating with a mixed solution of polymer coating agent and lithium salt; the separator is pretreated by mixing the lithium solid electrolyte pretreated by polymer coating agent and lithium salt with conductive additives and binders, and then coating it onto one surface of the separator to obtain a pretreated separator, wherein the surface of the pretreated separator is in contact with the positive electrode.
2. The lithium-sulfur battery according to claim 1, characterized in that, The composite cathode material also contains conductive additives, binders, and dispersants.
3. The lithium-sulfur battery according to claim 1, characterized in that, The carbon is porous carbon, and sulfur is at least partially embedded in the porous carbon.
4. The lithium-sulfur battery according to claim 1, characterized in that, The mass content of lithium solid electrolyte in electrolyte-doped sulfur / carbon composite cathode materials is 1%-30%.
5. The lithium-sulfur battery according to claim 1, characterized in that, The preparation method of the electrolyte-doped sulfur / carbon composite cathode material includes the following steps: S1. By grinding or ball milling sulfur and porous carbon, the resulting mixture is heated at 150℃-170℃ for 4-12 hours under vacuum or in an argon-filled environment, and then naturally cooled to room temperature to obtain a sulfur / carbon composite. S2. The pretreated lithium solid electrolyte is ground and mixed with the sulfur / carbon composite obtained in step S1 to obtain a lithium solid electrolyte-doped sulfur / carbon composite, which is then mixed with conductive additives, binders and dispersants to obtain the electrolyte-doped sulfur / carbon composite cathode material. The lithium solid electrolyte is selected from Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 0.55 La 0.35 One or more of TiO3.
6. The lithium-sulfur battery according to claim 5, characterized in that, The polymer coating agent is selected from polyvinylidene fluoride-hexafluoropropylene, polyoxyethylene ether, polyvinylidene fluoride, polydopamine, polyvinyl alcohol, polycaprolactone, polyvinyl carbonate, polypropylene carbonate, polymethyl methacrylate, lithium polystyrene sulfonate, and poly(ethylene glycol) methyl ether methacrylate; the lithium salt is selected from lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium bis(difluorosulfonyl)imide, or lithium bis(trifluoromethyl)sulfonylimide.
Citation Information
Patent Citations
Lithium-sulfur battery
CN107665966A
Lithium-sulfur battery
WO2015136197A1